The Role of Resource Allocation in Linking Enterprise Risk Management to Competitive Advantage of Small and Medium- Sized Enterprises - Zhang, Yangfeng (International Review of Management and Marketing, 2026)
The purpose of this study was to examine the role of resource allocation (RA) in linking enterprise risk management (ERM) to competitive advantage (CA) among medium-sized manufacturing enterprises in Shanghai, China, while exploring the moderating effect of innovation capability (IC). The study aimed to provide empirical insights into how ERM practices can be transformed into sustained organizational performance through effective resource deployment in a highly competitive and dynamic industrial context. A quantitative research design was adopted, and primary data were collected from 214 operations managers and business supervisors using structured questionnaires. The measurement scales were adapted from validated instruments in prior studies. Data analysis was conducted using SPSS, including descriptive statistics, reliability analysis, correlation analysis, and multiple regression to test direct, mediating, and moderating effects among the constructs. The results indicate that ERM has a significant positive impact on CA both directly and indirectly through RA. Furthermore, IC was found to strengthen the effect of RA on CA significantly. These findings emphasize the strategic importance of integrating risk management with resource deployment and fostering innovation to achieve sustained competitive performance. This study contributes to the literature by examining SMEs in Shanghai, highlighting the combined mediating and moderating mechanisms linking ERM, RA, and innovation to CA. Practically, it offers guidance for managers to implement risk-informed resource strategies and enhance IC to maintain resilience and competitiveness in emerging market contexts.